PENGARUH E-KUALITAS LAYANAN DAN PERSEPSI HARGA MEMEDIASI KEPUASAN PELANGGAN TERHADAP LOYALITAS KONSUMEN PADA E-COMMERCE LAZADA - Anik Pujianti; Janfry Sihite (Journal of Fundamental Management (JFM), 2023)
This study aims to examine and analyze the effect of e-service quality and price perception mediating customer satisfaction on consumer loyalty in ecommerce Lazada. The population in this study is millennial and gen z people who make online transactions more or less 2 times a month. The number of samples used in this study were 125 respondents with a quantitative descriptive approach. Data analysis using Partial Least Square (PLS). This study proves that e-service quality has a positive and significant effect on customer satisfaction. Price perception has no positive and significant effect on customer satisfaction. E-service quality has a positive and significant effect on consumer loyalty. price perception has a positive and significant effect on consumer loyalty. Customer satisfaction has a positive and significant effect on consumer loyalty.